2020
DOI: 10.1055/a-1180-9094
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Success Rate of Intracytoplasmic Sperm Injection with Azoospermic Male Patients

Abstract: Introduction Azoospermia affects about 1% of men, of whom up to 15% inquire about infertility treatment. Information about predictive factors for these couples is very limited. Patients, Materials and Methods We performed a retrospective analysis of the clinical records of 118 cycles of intracytoplasmic sperm injection treatment after testicular sperm extraction for male azoospermia carried out between January 2008 and October 2015. Of those, 66 were first, 35 second, and 17 third cycles. Statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Our study found a statistically significant association between number of embryos transferred and clinical pregnancy rates and, in particular, two embryos conferred the most chance of clinical pregnancy. A similar retrospective analysis of 118 TESE/ICSI treatments identified that the number of embryos transferred is positively associated with clinical pregnancy success (27). A recent Cochrane review found that there was a higher (46%) chance of live birth following a single cycle of transferring two embryos than one embryo (27-35%) (28).…”
Section: Jrimentioning
confidence: 99%
“…Our study found a statistically significant association between number of embryos transferred and clinical pregnancy rates and, in particular, two embryos conferred the most chance of clinical pregnancy. A similar retrospective analysis of 118 TESE/ICSI treatments identified that the number of embryos transferred is positively associated with clinical pregnancy success (27). A recent Cochrane review found that there was a higher (46%) chance of live birth following a single cycle of transferring two embryos than one embryo (27-35%) (28).…”
Section: Jrimentioning
confidence: 99%